Cartilage organoids for cartilage development and cartilage-associated disease modeling - Lin, Weiping; Wang, Min; Xu, Liangliang; Tortorella, Micky; Li, Gang (Frontiers in Cell and Developmental Biology, 2023)
Cartilage organoids have emerged as powerful modelling technology for recapitulation of joint embryonic events, and cartilage regeneration, as well as pathophysiology of cartilage-associated diseases. Recent breakthroughs have uncovered “mini-joint” models comprising of multicellular components and extracellular matrices of joint cartilage for development of novel disease-modifying strategies for personalized therapeutics of cartilage-associated diseases. Here, we hypothesized that LGR5-expressing embryonic joint chondroprogenitor cells are ideal stem cells for the generation of cartilage organoids as “mini-joints” ex vivo “in a dish” for embryonic joint development, cartilage repair, and cartilage-associated disease modelling as essential research models of drug screening for further personalized regenerative therapy. The pilot research data suggested that LGR5-GFP-expressing embryonic joint progenitor cells are promising for generation of cartilage organoids through gel embedding method, which may exert various preclinical and clinical applications for realization of personalized regenerative therapy in the future.